Prolonged Primary Hyperparathyroidism: Are We Overtreating our Patients? - Mosli, Hala (Journal of King Abdulaziz University: Medical Sciences, 2024)
Primary Hyperparathyroidism is increasing in incidence likely due to enhanced screening and diagnostic methods, and while most cases are asymptomatic and discovered incidentally, current recommendations encourage surgical management for patients who are symptomatic or those who have evidence of organ involvement, or those who meet the criteria for surgical intervention. However, in some cases who have had long-standing disease with minimal impact, a more conservative approach may be prudent. This case report presents a 68-year-old retired physician with type 2 diabetes managed in the Endocrinology clinic, incidentally discovered to have long-standing primary hyperparathyroidism (PHPT) during routine lab investigations. Despite a history of recurrent kidney stones and elevated parathyroid hormone (PTH) levels over 40 years, the patient remains relatively asymptomatic with minimal end-organ involvement. Current diagnostic and therapeutic recommendations suggest surgical intervention; however, the patient, given his lengthy disease course, opts for a conservative approach. This case prompts a reconsideration of individualized management strategies in the era of precision medicine.